PERANCANGAN DAN PEMBUATAN MODEL SIMULASI TEMPAT PARKIR OTOMATIS DENGAN MENGGUNAKAN BAHASA PEMROGRAMAN C DAN MIKROKONTROLER ATMEGA 32 - , MARJUKI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The number of users of personal transport equipment from time to time resulted in a rapidly growing parking space available can not accommodate the number of vehicles. Especially for four-wheeled vehicle users who sometimes use the side of the road to the parking lot because the parking lot is full. As a result of congestion caused by road is getting narrower as used for the parking lot can not be avoided. One way to overcome the limitations of land used for the park is to create a system of automatic car park or also called APS (Automated Parking System). The system is located in a park-storey building which can cut the use of large area with high rise building methods. In this study conducted in the design and manufacture of the model/prototype automated car park. This study aims to create a prototype of an automatic car park using aluminum materials. Researchers using a rotary potentiometer adc or 10k as a sensor for determining the position of the slot parking space. From the research that has been done we got the result that the prototype of an automatic car park successfully created with a size of 50 x 30 x 30 and the aluminum plate and profile shape. Rotary adc used as a sensor to determine the position of the slot with a parking space using microcontroller programming and software CodeVision ATMEGA 32 AVR .